Embroidery Leaf Shape Dipole Antenna Performances and Characterisation - N. J. Ramly; M. K. A. Rahim; N. A. Samsuri; H. A. Majid (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this paper, leaf shape textile antenna in ISM band has been chosen to study. The operating frequency of the dipole antenna is 2.45GHz. The effect of conductive threads with three different types of sewing has been analysed. The first type of sewing leaf shape dipole antenna is to stitch around itself and embroidered into a fleece fabric with circular follow by vertical and horizontal stitch respectively. From measured return loss, the antenna with circular stitch shows better performances with optimum resonances compared with the two types of stitching. The measured results confirm that the circular stitch is more suitable for leaf shape dipole antenna design. Thus it can be concluded that different stitch gives different results for leaf shape dipole antenna.